MODELING AND OPTIMIZATION OF BAKERY YEAST (SACCHAROMYCES CEREVISIAE) VIABILITY BY USING EXPERIMENTAL DESIGN PROCEDURE - ANA-MARIA GEORGESCU; DUMITRA RADUCANU (Journal of Engineering Studies and Research)
This paper presents the application of kn experiment design procedure for simulation and optimization of growth capacity for baker’s yeast, Saccharomyces cerevisiae. There were performed 27 experiments according to the experimental design procedure. The input variables were: the amount of carbohydrates (X1), temperature (X2) and pH (X3) and the output variable was the autolyzed cells (Y). The optimal conditions for growth parameters of Saccharomyces cerevisiae were obtained for an amount of carbohydrates (glucose) of 46.8 g·L-1, a temperature of 30oC and a pH of 5.7.